Influence of Process Stability and Part Positioning on Morphological Properties of Designed Materials Produced by Laser‐Based Powder Bed Fusion of Metals on a Multi‐Laser Machine. Issue 8 (17th January 2022) - Albert, Johannes; Hermann, Oliver; Purschke, Simon; Rule, David; Fleck, Claudia
Abstract : Porous structures made from high temperature superalloys are candidates for high‐efficiency cooling applications. In this kind of product, the repeatability of flow‐relevant elements is of high interest in multiple aspects—e.g., performance, component lifetime, and costs. Configurable open‐porous materials—addressed here as designed materials (DMs)—can be produced via laser‐based powder bed fusion of metals (PBF‐LB/M) by process parameter adaptions. With the high temperature superalloy Haynes 282 DM's manufacturability was previously demonstrated on a multi‐laser EOS M 400‐4 PBF‐LB/M machine. The influence of part positioning on the respective relative density of such structures and scatter were shown and tolerance equations developed. Hence, herein, the main objective is following up on the repeatability of morphological DM properties. Therefore, DM's mean pore diameter, mean strut diameter, and surface ratio are analyzed via microcomputed tomography (μCT). A positional scatter assessment is performed. Moreover, attention is paid to the repeatability of the investigated properties over different laser quadrants and build jobs. The identified scatter is utilized in the tolerance equations formulated in this research. Furthermore, potential correlations among the properties—relative density, mean pore diameter, mean strut diameter, and surface ratio—are examined. Abstract : Laser‐based powder bed fusion of metals (PBF‐LB/M) was used to build open‐porous structures—designed materials (DMs)—out of a high temperature superalloy. Morphological properties were analyzed via micro computed tomography. The objective was investigating positioning influence, process stability, and correlations between these properties. The results of positioning influence and scatter were used to formulate tolerance equations.